2022
DOI: 10.1007/s00023-022-01232-7
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Generalized Wannier Bases Implies Chern Triviality in Non-periodic Insulators

Abstract: We investigate the relation between the localization of generalized Wannier bases and the topological properties of two-dimensional gapped quantum systems of independent electrons in a disordered background, including magnetic fields, as in the case of Chern insulators and quantum Hall systems. We prove that the existence of a well-localized generalized Wannier basis for the Fermi projection implies the vanishing of the Chern character, which is proportional to the Hall conductivity in the linear response regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Proof. Without loss of generality, we can assume that m > l. To compute the sum in ( 14), we use the Cauchy-Maclaurin criterion adapted to our setting in same spirit as in [80]. The main idea is to estimate the sum from above by using an integral.…”
Section: A Elementary Lemmasmentioning
confidence: 99%
“…Proof. Without loss of generality, we can assume that m > l. To compute the sum in ( 14), we use the Cauchy-Maclaurin criterion adapted to our setting in same spirit as in [80]. The main idea is to estimate the sum from above by using an integral.…”
Section: A Elementary Lemmasmentioning
confidence: 99%
“…In [22] it is shown that GWBs can be used to investigate topological and transport properties of non-periodic gapped quantum systems. In particular, the Fermi projections that admit an exponentially localized (or just a well-localized [22]) GWB with a uniformly discrete set D, are Chern trivial in the sense that their Chern character is zero.…”
Section: Introductionmentioning
confidence: 99%
“…In [22] it is shown that GWBs can be used to investigate topological and transport properties of non-periodic gapped quantum systems. In particular, the Fermi projections that admit an exponentially localized (or just a well-localized [22]) GWB with a uniformly discrete set D, are Chern trivial in the sense that their Chern character is zero. As well known, the Chern character is proportional to the Hall conductivity, thus showing that topological quantum transport and well-localized generalized Wannier bases cannot coexist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The localization properties of Wannier functions also have a direct bearing on the topological properties of electronic bands. [5][6][7][8][9]. Exponentially localized Wannier functions can be constructed if and only if the Chern number and Hall conductivity of the corresponding filled band(s) are zero [5,10,11].…”
mentioning
confidence: 99%